From Screen to Speech: Utilizing Movie for Creative Story Completion in EFL Class - Fajriantini, Aisyah (BEduManagers Journal : Borneo Educational Management and Research Journal, 2025)
This qualitative case study explores the integration of movie clips with the story completion technique for teaching EFL speaking skills. Focusing on one lecturer’s experience at a private university in East Java, data from a semi-structured interview were analyzed thematically. Findings indicate that this integrated approach effectively boosts student motivation, engagement, and creative thinking during speaking activities. It provides authentic language exposure and fosters narrative fluency. While technical issues with audio-visual equipment pose a challenge, the strategy is deemed highly beneficial. The study concludes that combining movies with story completion is a valuable pedagogical tool for enhancing oral proficiency, recommending careful content selection and technical preparedness.